3-Nitrooxypropanol Decreased Enteric Methane Production From Growing Beef Cattle in a Commercial Feedlot: Implications for Sustainable Beef Cattle Production - Alemu, Aklilu W.; Pekrul, Liana K. D.; Shreck, Adam L.; Booker, Calvin W.; McGinn, Sean M.; Kindermann, Maik; Beauchemin, Karen A. (Frontiers in Animal Science, 2021)
Effects of the investigational inhibitor 3-nitrooxypropanol (3-NOP) on animal performance, health and enteric methane (CH4) production of beef cattle fed a backgrounding diet were evaluated in a commercial feedlot. Two concurrent studies were conducted: a large pen study (4,048 cattle, 8 pens per treatment) to measure animal performance and health and a small pen study (25 cattle per treatment) to measure enteric CH4 emissions (using the GreenFeed system). Within study, animals (initial body weight ± SD, 282 ± 8 kg) were assigned in a completely randomized design to one of two treatments: control, fed a backgrounding diet (70% corn or barley silage, 30% barley grain concentrate; dry matter (DM) basis) and 3-NOP, fed the backgrounding diet containing 3-NOP. The treatment group in the large pen study received increasing doses of 3-NOP over 12 ± 3 d for adaptation and followed by the final dose of 200 mg/kg of DM for 108 ± 8 d. Animals in the CH4 emissions study received a basal diet or a basal diet with 3-NOP, with the dose increased every 28 d: low (150 mg/kg DM), medium (175 mg/kg DM), and high (200 mg/kg DM). In the large pen study, average daily gain and animal health variables were not affected by 3-NOP, but DM intake (DMI) tended to decrease (P = 0.06) by 2.6% relative to control (8.07 kg/d), while gain:feed ratio tended to improve (P = 0.06) by 2.5% relative to control (0.161 kg weight gain/kg DMI). In the small pen study, compared with control (10.4 kg/d), average DMI (basal diet + pellet offered during CH4 measurement) was decreased by 5.4% (P = 0.02). On average, addition of 3-NOP decreased (P = 0.001) CH4 emissions (g/d) by 25.7% and yield (g CH4/kg DMI) by 21.7%. In conclusion, supplementing a backgrounding diet with 3-NOP decreased CH4 yield and tended to improve feed efficiency of beef cattle fed in a commercial feedlot with no negative impacts on animal health. 3-Nitrooxypropanol has great potential to reduce CH4 emissions from the beef industry to improve its environmental sustainability.